Punctate palmoplantar keratoderma: A case report and literature review - J P Prathibha; Vijay Venkataraj Aithal (Wolters Kluwer Medknow Publications, 2023)
Punctured palmoplantar keratodermas are rare autosomal-dominant keratodermas presenting as asymptomatic, tiny hyperkeratotic pigmented papules on the palms and soles. We present a rare case of punctate palmoplantar keratoderma type 1 extending to the dorsum of the foot with pes cavus deformity of the foot. We did the literature review.